Unraveling the Possibilities of Monoclonal Protein Migration, Identification, and Characterization in SPEP on Capillary Zone Electrophoresis - Prisi, Shailata; Khurana, Vatsala; Saijpaul, Rajni; Verma, Rashmi; Chandra, Lal; Koner, Bidhan Chandra (Journal of Laboratory Physicians, 2022)
Serum protein electrophoresis (SPEP) is a method by which proteins present in serum are separated into different fractions based on their molecular weight and electric charge. Presence of M spike, composed of monoclonal protein, on electrophoretogram is a characteristic finding that can be seen in monoclonal gammopathies like multiple myeloma. M spike is most commonly seen in the gamma region however, the M-spike can be observed in fraction other than the Y fraction as well i.e. in the beta region and rarely alpha region. Here we have enumerated few cases where M protein has been seen in fractions other than the gamma region. Thus one needs to be cautious about the variable appearance of M-spike during interpretation of SPEP as some physiological proteins if elevated can also give rise to similar spike sometimes referred as pseudo monoclonal pattern.
Keywords: capillary zone electrophoresis; multiple myeloma; M-spike; monoclonal protein; variable migration